Current engagement with unreliable sites from web search driven by navigational search - Greene, Kevin T.; Pisharody, Nilima; Meyer, Lucas A.; Pereira, Mayana; Dodhia, Rahul; Lavista Ferres, Juan M. (Science Advances, 2024)
Do search engine algorithms systematically expose users to content from unreliable sites? There is widespread concern that they do, but little systematic evidence that search engine algorithms, rather than user-expressed preferences, are driving current exposure to and engagement with unreliable information sources. Using two datasets totaling roughly 14 billion search engine result pages (SERPs) from Bing, the second most popular search engine in the U.S., we show that search exposes users to few unreliable information sources. The vast majority of engagement with unreliable information sources from search occurs when users are explicitly searching for information from those sites, despite those searches being an extremely small share of the overall search volume. Our findings highlight the importance of accounting for user preference when examining engagement with unreliable sources from web search.